Anxiety, ego depletion and sports performance - Englert, E.; Bertrams, A. (Journal of Sport & Exercise Psychology, 2012)
In the present article, we analyzed the role of self-control strength and state anxiety in sports performance. We tested the hypothesis that self-control strength and state anxiety interact in predicting sports performance on the basis of two studies, each using a different sports task (Study 1: performance in a basketball free throw task, N = 64; Study 2: performance in a dart task, N = 79). The patterns of results were as expected in both studies: Participants with depleted self-control strength performed worse in the specific tasks as their anxiety increased, whereas there was no significant relation for participants with fully available self-control strength. Furthermore, different degrees of available self-control strength did not predict performance in participants who were low in state anxiety, but did in participants who were high in state anxiety. Thus increasing self-control strength could reduce the negative anxiety effects in sports and improve athletes` performance under pressure.